A 3-Year-Old Girl With Recent Onset of Seizures and Asymmetric Hypermetabolic Activity on 18F-FDG PET/CT. (June 2021) - Hayrapetian, Artineh; Dambroz, Andrezza; Seyedroudbari, Ameen; Schelbert, Heinrich; Gupta, Pawan
Abstract : Abstract: A 3-year-old, previously healthy girl started having clusters of seizures, not responsive to multiple antiepileptic medications. High-dose prednisone and intravenous immunoglobulin could partially control the seizures. Lumbar puncture and CT were normal. An MRI showed right hemispheric injury and atrophy compatible with clinical suspicion of Rasmussen encephalitis. Neurological 18 F-FDG PET/CT demonstrated asymmetric hypermetabolic activity in the right frontal and parietal lobes compatible with active inflammation. The patient underwent a right functional hemispherectomy, which confirmed clinical suspicion of Rasmussen encephalitis. During the follow-up, the patient has continued to take phenobarbital and levetiracetam (Keppra), with no recurrence of seizures.